Human DMBT1-Derived Cell-Penetrating Peptides for Intracellular siRNA Delivery - Martina Tuttolomondo; Cinzia Casella; Pernille Lund Hansen; Ester Polo; Luciana M. Herda; Kenneth A. Dawson; Henrik J. Ditzel; Jan Mollenhauer (Molecular Therapy: Nucleic Acids, 2017)
Small interfering RNA (siRNA) is a promising molecule for gene therapy, but its therapeutic administration remains problematic. Among the recently proposed vectors, cell-penetrating peptides show great promise in in vivo trials for siRNA delivery. Human protein DMBT1 (deleted in malignant brain tumor 1) is a pattern recognition molecule that interacts with polyanions and recognizes and aggregates bacteria. Taking advantage of these properties, we investigated whether specific synthetic DMBT1-derived peptides could be used to formulate nanoparticles for siRNA administration. Using an electrophoretic mobility shift assay and UV spectra, we identified two DMBT1 peptides that could encapsulate the siRNA with a self- and co-assembly mechanism. The complexes were stable for at least 2 hr in the presence of either fetal bovine serum (FBS) or RNase A, with peptide-dependent time span protection. ζ-potential, circular dichroism, dynamic light scattering, and transmission electron microscopy revealed negatively charged nanoparticles with an average diameter of 10–800 nm, depending on the reaction conditions, and a spherical or rice-shaped morphology, depending on the peptide and β-helix conformation. We successfully transfected human MCF7 cells with fluorescein isothiocyanate (FITC)-DMBT1-peptide-Cy3-siRNA complexes. Finally, DMBT1 peptides encapsulating an siRNA targeting a fluorescent reporter gene showed efficient gene silencing in MCF7-recombinant cells. These results lay the foundation for a new research line to exploit DMBT1-peptide nanocomplexes for therapeutic siRNA delivery. Keywords: DMBT1, cell-penetrating peptides, cellular uptake, transfection, siRNA delivery, RNAi, silencing, gene knockdown, nanoparticles, nanotherapy